A Place for Project Management in English Studies and Communication Studies Curricula - Kampf, Constance; Isohella, Suvi (Nordic Journal of English Studies, 2009)
In this paper, we argue for a place for project management in the English Studies and Communication Studies curricula, often the home of Technical Communication programs, in order to offer students an opportunity to apply their language, discourse analysis, analytical skills, and creativity in a transitional setting which can serve as a bridge between the classroom and the workplace. The perceptions of the need for project management are examined with respect to interviews of Finnish technical communication graduates, and an example of a project management course focused on the communication aspects inherent in project management tools and process from a Project Management course taught simultaneously at the Aarhus School of Business and the Helsinki School of Economics is described, including examples from Project Management assignments which correspond to problem-solving skills. In addition, some of the project management genres are briefly discussed and related to key skills emerging from English studies and Technical Communication curricula.